The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/09553001003734543
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the kinetics of γ-H2AX fluorescence decay after exposure to low and high LET radiation

Abstract: gamma-H2AX loss kinetics follows a bi-exponential decline with two definite decay times independent of LET. The higher contribution of the slow component determined for carbon ion exposure is thought to reflect the increased amount of complex DSB induced by high LET radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 48 publications
7
66
0
Order By: Relevance
“…Consistent with prior findings, similar numbers of -H2AX foci are formed after low LET and high LET radiation but there are more remaining -H2AX foci at 24 h after high LET radiation (20% of initial foci remaining after alpha particle, 120 keV/µm, compared to less than 10% after gamma ray) [54,97,98]. In addition, the repair of DNA DSB appears to consist of two kinetic components, a fast phase and a slow phase, where most of the DNA DSBs caused by high LET radiation is repaired [97]. Studies in our lab with anti-HER2 Trastuzumab labeled alpha-particle emitter 213 Bi also see the same trend where higher fraction of -H2AX foci remained at 24 h compared to gamma irradiation (unpublished data).…”
Section: Dna Dsb Repair After High Let Radiationsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with prior findings, similar numbers of -H2AX foci are formed after low LET and high LET radiation but there are more remaining -H2AX foci at 24 h after high LET radiation (20% of initial foci remaining after alpha particle, 120 keV/µm, compared to less than 10% after gamma ray) [54,97,98]. In addition, the repair of DNA DSB appears to consist of two kinetic components, a fast phase and a slow phase, where most of the DNA DSBs caused by high LET radiation is repaired [97]. Studies in our lab with anti-HER2 Trastuzumab labeled alpha-particle emitter 213 Bi also see the same trend where higher fraction of -H2AX foci remained at 24 h compared to gamma irradiation (unpublished data).…”
Section: Dna Dsb Repair After High Let Radiationsupporting
confidence: 87%
“…Carboxy-terminal phosphorylation of histone H2AX is the earliest cellular response to DNA DSB that accumulates at the sites of DSB quickly (within minutes of the damage) [96]. Consistent with prior findings, similar numbers of -H2AX foci are formed after low LET and high LET radiation but there are more remaining -H2AX foci at 24 h after high LET radiation (20% of initial foci remaining after alpha particle, 120 keV/µm, compared to less than 10% after gamma ray) [54,97,98]. In addition, the repair of DNA DSB appears to consist of two kinetic components, a fast phase and a slow phase, where most of the DNA DSBs caused by high LET radiation is repaired [97].…”
Section: Dna Dsb Repair After High Let Radiationsupporting
confidence: 71%
“…It is proposed here to asses these irradiation modes by analyzing initial 1-h and late 24-h DNA DSB numbers in HeLa cells, in order to address foci numbers after different repair times. Schmid et al showed that gamma-H2AX loss kinetics follows a bi-exponential decline with two distinct decay time constants independent of LET but with a larger fraction of damage belonging to the larger decay time constant for high-LET irradiation (Schmid et al 2010a). In the current setting, these results were extended to assess the differences in temporal modes between pulsed and continuous irradiation .…”
Section: Introductionmentioning
confidence: 98%
“…The majority of DSBs are repaired in 24 h. γH2AX is a hallmark of DSB recognition and repair. Fewer γH2AX foci represent a more rapid repair of DSBs and higher radioresistance (19)(20)(21)(22)(23)(24). RAD51 is an important protein involved in homologous recombination processes.…”
Section: Discussionmentioning
confidence: 99%